Pengaruh Komunikasi Dan Gaya Kepemimpinan Terhadap Kepuasan Kerja Pegawai Pada Kantor Dinas Pekerjaan Umum Dan Penataan Ruang Kabupaten Bima - Yuliarti Yuliarti; Mukhlis Mukhlis (JURNAL RISET MANAJEMEN (JURMA), 2023)
This study aims to determine the effect of communication and leadership style on employee job satisfaction at the Department of Public Works and Spatial Planning, Bima Regency. The type of research used in this study is a quantitative approach. The population in this study were all employees of the Bima Regency Public Works and Spatial Planning Office, namely 204 people, with a total sample consisting of 88 respondents. The sampling technique used was purposive sampling with data collection techniques using a questionnaire. The data analysis method used is multiple linear regression analysis with the SPSS (Statistical Product and Service Solution) application tool version 26. Based on the results of the t test in this study it shows that: 1. Communication has a positive and significant influence on employee job satisfaction. Public Works and Spatial Planning Office of Bima Regency; 2. Leadership style has a positive and significant influence on job satisfaction of employees of the Public Works and Spatial Planning Office of Bima Regency.